2021
DOI: 10.1007/s42452-021-04880-2
|View full text |Cite
|
Sign up to set email alerts
|

Screening of potential antidiabetic phytochemicals from Gongronema latifolium leaf against therapeutic targets of type 2 diabetes mellitus: multi-targets drug design

Abstract: Diabetes mellitus (DM) is the most predominant group of metabolic disorders wreaking havoc on the wellbeing of man, with type 2 diabetes mellitus (type 2 DM) accounting for most DM related cases. This study, hence, investigated the antidiabetic potential of Gongronema latifolium leaf fractionated compounds against proteins implicated in different molecular pathways related to the onset and progression of type 2 DM. A total of fifteen proteins that can act as type 2 DM therapeutic targets were identified from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The mechanisms of action of medicinal plants in diabetes management include the regeneration of β cells and the improvement of insulin secretion from the pancreas, increased glucose uptake by muscles and adipose tissue, decreased gluconeogenesis, and the inhibition of intestinal α-glucosidase [ 99 ]. Recent studies have identified GLP-1 modulatory activity in medicinal plants [ 100 , 101 , 102 ], which holds promise for diabetes management. Table 1 provides an overview of medicinal plants with GLP-1-inducing activity.…”
Section: Medicinal Plantsmentioning
confidence: 99%
“…The mechanisms of action of medicinal plants in diabetes management include the regeneration of β cells and the improvement of insulin secretion from the pancreas, increased glucose uptake by muscles and adipose tissue, decreased gluconeogenesis, and the inhibition of intestinal α-glucosidase [ 99 ]. Recent studies have identified GLP-1 modulatory activity in medicinal plants [ 100 , 101 , 102 ], which holds promise for diabetes management. Table 1 provides an overview of medicinal plants with GLP-1-inducing activity.…”
Section: Medicinal Plantsmentioning
confidence: 99%
“…Based on the docking results, the infusion of O. majorana, another member of the Lamiaceae family, in which quercetin was detected [71], may also be an ideal candidate for the inhibition of AR [72]. In addition, caftaric acid, a phenolic acid of E. purpurea [73,74], exhibited important binding affinity toward AR [75], placing Echinacea among the herbs with possible action against hyperglycemia and metabolic syndrome induced by high blood sugar levels [76].…”
Section: Phytochemical Phenolic Profile Of the Examined Infusion By L...mentioning
confidence: 99%
“…Computational modeling prediction of the ligand affinity for molecular targets in diabetes has been widely studied [23,24]. The inhibitory potential of compounds from the alliaceous plant protein tyrosine phosphatase 1B (PTP1B) has been predicted in silico as a possible mechanism of antidiabetic effects [25,26]. Glucokinase (GK) is an essential enzyme in glucose metabolism and a potential therapeutic target in type 2 diabetes [27].…”
Section: Introductionmentioning
confidence: 99%